Impact of Credit Risk Management in Profitability of Commercial Banks of Nepal - Dahal, Rabin; Dhungana, Deepa Panthi (Nepalese Journal of Economic Studies, 2025)
This study investigates the key determinants of bank profitability in Nepal over the period 2004 to 2025, focusing on internal bank-specific factors. The analysis employs panel data regression techniques using both fixed effects (FE) and random effects (RE) models to examine the impact of the capital adequacy ratio (CAR), non-performing loan ratio (NPLR), and bank size on return on equity (ROE). The study is motivated by the growing need for effective risk management and sustainable financial performance within Nepal’s evolving banking sector. Results from the Hausman test favor the fixed effects model, indicating that unobserved, bank-specific characteristics are correlated with the explanatory variables. The FE model findings reveal that higher capital adequacy and larger bank size have a statistically significant positive effect on profitability, while a higher level of nonperforming loans negatively impacts ROE. In contrast, the random effects model shows weaker and largely insignificant relationships. These findings underscore the critical role of sound capital management and credit risk control in enhancing the profitability and financial health of commercial banks in Nepal.